Mg/Al-CH, Ni/Al-CH and Zn/Al-CH, as adsorbents for Congo Red removal in aqueous solution - Siregar, Patimah Mega Syah Bahar Nur; Normah; Juleanti, Novie; Wijaya, Alfan; Palapa, Neza Rahayu; Mohadi, Risfidian; Lesbani, Aldes (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2021)
In this study, chitosan was extracted from shrimp shells by demineralization and deproteination processes. The extracted chitosan was used to modify the layered double hydroxide and used as an adsorbent for the removal of congo red from aqueous solutions. Composites were successfully synthesized using M2+/Al (M2+ = Zn, Mg, Ni) and chitosan (CH) and the samples obtained were characterized using XRD and FTIR. The X-ray diffraction (XRD) pattern appeared at the layered double hydroxide peak of 2? = 11.63°; 23.00°; 35.16°; and 61.59° and chitosan at 2? = 7.93° and 19.35. The composite appearing in the layered double hydroxide and chitosan indicated that the composite material has been successfully synthesized. The XRD diffraction patterns of Zn/Al-CH, Ni/Al-CH, and Mg/Al-CH showed low crystallinity. The Fourier Transform Infrared (FTIR) spectra verifying absorption spectrum showed the presence of two bands at 3448 cm-1, 1382cm-1 characteristic to both chitosan and LDH. Adsorption of Congo Red (CR) followed the pseudo-second-order and Langmuir isotherm models. The adsorption capacities of Zn/Al-CH, Ni/Al-CH, and Mg/Al-CH were 181.818 mg/g, 227.273 mg/g, and 344.828 mg/g, respectively. The layered double hydroxide-chitosan composite adsorption was endothermically characterized by positive enthalpy and entropy values. On the other hand, the adsorption spontaneously was characterized by a negative Gibbs free energy value. The composites in this study were formed from LDH modified from chitosan extracted from shrimp shells to form Zn/Al-CH, Ni/Al-CH, and Mg/Al-CH. The results of the characterization showed a number of characteristics that resembled the constituent materials in the form of LDH and chitosan. After being applied as an adsorbent to absorb Congo red dye, it then showed the most effective results using Mg/Al-CH adsorbent with an adsorption capacity of 344.828 mg/g.